2021
DOI: 10.3390/ijerph18147666
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Factors in Adolescent Well-Being: Family and Parental Relationships

Abstract: Health-related quality of life, teachers’ opinion of academic performance and self-perceived health are indicators of well-being in the adolescent stage. Some variables, such as those related to the quality of family and parental relationships, may influence these indicators and thus condition well-being during this stage of life and beyond. In this research, the aforementioned variables are analyzed jointly. It is a cross-sectional study in which 1375 adolescent schoolchildren between 11 and 18 years of age p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
3
18
0
3
Order By: Relevance
“…Behaviors having a positive influence on the functioning of the cardiovascular system include regular, appropriate physical activity that, in the case of adults, reduces general mortality and CVD morbidity by 20–30% [ 20 , 21 ]. Family relationships have a huge influence on the formation of health-promoting attitudes among children [ 22 ]. It has been proven that physical activity habits established in childhood are continued in adulthood [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behaviors having a positive influence on the functioning of the cardiovascular system include regular, appropriate physical activity that, in the case of adults, reduces general mortality and CVD morbidity by 20–30% [ 20 , 21 ]. Family relationships have a huge influence on the formation of health-promoting attitudes among children [ 22 ]. It has been proven that physical activity habits established in childhood are continued in adulthood [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to meet the priority of the parents, the child had to obtain good aquatic competences to ensure a safe future that prevents the risk of drowning [31,32], In the literature is evident the relation between the parent's involvement and the child's behavior [33]. It is known that, some variables such as parental relationship may influence the well-being of the child [34]. In particular, aquatic experience of the child based on teacher centered pedagogy (LI), positively evaluated by the parents, could slow down the natural and optimal learning process [35].…”
Section: Parents' Preliminary Interview and Gt Related To Parents' Perceptionmentioning
confidence: 99%
“…The World Health Organization defined an adolescent as any individual between ages 10 and 24 years, and adolescence as a period of life in which adolescents have health and developmental needs [4][5][6]. Adolescence can be a time of both disorientation and discovery, a transitional period that can raise questions of independence and identity as adolescents cultivate their sense of self, during which they make choices about physical activity (PA) behavior [7,8]. It is a time to develop healthy behaviors, knowledge, and skills that will be important later in life.…”
Section: Introductionmentioning
confidence: 99%
“…NCDs are the result of a combination of genetic, physiological, environmental, and behavioral factors. The statistics on NCDs indicated that they account for more than a third of all deaths in South Africa [8]. Notably, there are increases in risks related to NCDs such as physical inactivity.…”
Section: Introductionmentioning
confidence: 99%